UJI PROKSIMAT UBUR-UBUR (Rhizostoma Pulmo) SEGAR DAN KERING - Abdiani, Ira Maya; Kirana, Elsa; Yulianto, Agus; Akhmadi, Mohammad Fadnan; Simanjuntak, Ricky Febrinaldy; Imra, Imra (Jurnal Harpodon Borneo, 2022)
Tarakan city has the potential of marine biological resources that are very abundant such as fish, shrimp, seaweed and even jellyfish. Jellyfish is one of the aquatic commodities found in almost all marine waters of Indonesia. Jellyfish has the potential as a source of nutrient-rich foods that give high economic value. This is due to the lack of information about the nutritional content of jellyfish. The purpose of this study is to determine the proximate content of fresh and dry Rhizostoma Pulmo jellyfish. This research method using purposive sampling which followed sampling of jellyfish (R. pulmo) in Amal Lama Beach, sample preparation, calculation of yield and proximate analysis. Protein testing using the Semi Kjeldahl method, lemk testing using the Soxhlet method, testing water content using the gravimetric method, measuring carbohydrate using the by different method. Based on this study Proximat content found in fresh and dried jellyfish consist of 96,2% water content, 1% ash content, 34,5% protein content, 12,5% fat content, 47,9% carbohydrate content. Proximate levels dry jellyfish Â 58,78% water content is, 11 % ash content, 46,3 % protein content, 1.5% fat content and 39,9% carbohydrate content